2017
DOI: 10.1186/s13568-017-0414-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brewers’ spent grain as a novel media for yeast growth

Abstract: Brewers’ spent grain (BSG) is a by-product generated from the beer manufacturing industry, which is extremely rich in protein and fiber. Here we use low cost BSG as the raw material for the production of a novel growth media, through a bioconversion process utilizing a food grade fungi to hydrolyze BSG. The novel fermentation media was tested on the yeast Rhodosporidium toruloides, a natural yeast producing carotenoid. The yeast growth was analysed using the growth curve and the production of intracellular fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…As such, fermentation may enhance the amount of small free amino nitrogen molecules and serve as an effective nitrogen source for cultivating P. tricornutum cells. A similar trend was found in a study (Cooray, Lee, & Chen, 2017) which fermented another type of food by-product, brewers' spent grain (BSG), a protein and fiber rich by-product produced from the beer manufacturing industry. The authors reported increased amino acid content in fermented BSG media compared to unfermented BSG media.…”
Section: Growth Of P Tricornutum In Fermented Okara Media and Comparsupporting
confidence: 77%
“…As such, fermentation may enhance the amount of small free amino nitrogen molecules and serve as an effective nitrogen source for cultivating P. tricornutum cells. A similar trend was found in a study (Cooray, Lee, & Chen, 2017) which fermented another type of food by-product, brewers' spent grain (BSG), a protein and fiber rich by-product produced from the beer manufacturing industry. The authors reported increased amino acid content in fermented BSG media compared to unfermented BSG media.…”
Section: Growth Of P Tricornutum In Fermented Okara Media and Comparsupporting
confidence: 77%
“…Relative production of carotenoids; torularhodin, torulene and β-carotene by R. toruloides when grown in YPD, Fermented BSG (2%w/w glucose) and Unfermented BSG (2%w/w glucose) media [230].…”
Section: Figure 4mentioning
confidence: 99%
“…Growth curves for R. toruloides when grown in YPD, Unfermented BSG and Unfermented BSG (2%w/w glucose) media[230].…”
mentioning
confidence: 99%
See 2 more Smart Citations